Future directions for agent-based software engineering. (20th May 2009) - Winikoff, Michael
We briefly review the current state of play in the area of agent-based software engineering, and then consider, 'what next?' We discuss a range of marketing activities that will together help in making people from other communities aware of work in this area. We then outline a number of research topics that are seen as vital to the future of the field. Although (as always) more research is needed, recent progress in both research and industrial adoption has been most encouraging, and the future of agent-based software engineering looks bright.